Quality of life is an important criterion for the efficiency of targeted therapy for metastatic skeletal involvement in breast cancer - T. Yu. Semiglazova; V. V. Semiglazov; L. V. Filatova; P. V. Krivorotko; V. V. Kolarkova; V. F. Semiglazov (Опухоли женской репродуктивной системы)
Assessment of quality of life is an important, valid, informative, and cost-effective procedure for evaluating the efficiency of treatment in patients with breast cancer metastasizing to the bone, receiving therapy with bone-modifying agents, including targeted therapy with denosumab. The administration of denosumab significantly improves quality of life in patients with breast cancer metastasizing to the bone, by maintaining their general status, reducing the intensity of pain syndrome, and prevents osseous complications: pathological fractures, spinal cord compression, hypercalcemia, as well as the need for radiotherapy or surgery for bone metastases.